Food security and global environmental change: Emerging challenges - Ericksen, Polly J.; Ingram, John S.I.; Liverman, D.M. (Elsevier, 2009)
Most research linking global environmental change and food security focuses solely on agriculture: either the impact of climate change on agricultural production, or the impact of agriculture on the environment, e.g. on land use, greenhouse gas emissions, pollution and/or biodiversity. Important though food production is, many other factors also need to be considered to understand food security. A recent international conference on "Environmental Change and Food Security: Bridging Science, Policy and Development for Adaptation" included a range of papers that embraced the multiple dimensions of the food systems that underpin food security. The major conclusion from the conference was that technical fixes alone will not solve the food security challenge. Adapting to the additional threats to food security arising from major environmental changes requires an integrated food system approach, not just a focus on agricultural practices. Six key issues emerged for future research: (i) adapting food systems to global environmental change requires more than just technological solutions to increase agricultural yields; (ii) tradeoffs across multiple scales among food system outcomes are a pervasive feature of globalized food systems; (iii) within food systems, there are some key underexplored areas that are both sensitive to environmental change but also crucial to understanding its implications for food security and adaptation strategies; (iv) scenarios specifically designed to investigate the wider issues that underpin food security and the environmental consequences of different adaptation options are lacking; (v) price variability and volatility often threaten food security; and (vi) more attention needs to be paid to the governance of food systems.